Evaluation of Long-term Anatomic Changes Following Canaloplasty With Anterior Segment Spectral-domain Optical Coherence Tomography and Ultrasound Biomicroscopy. Issue 1 (January 2018) - Kuerten, David; Plange, Niklas; Becker, Jakob; Walter, Peter; Fuest, Matthias
Abstract : Background: To analyze long-term structural changes in conjunctiva, sclera and Schlemm canal (SC) with anterior segment optical coherence tomography (AS-OCT) and ultrasound biomicroscopy (UBM) following uncomplicated canaloplasty. Materials and Methods: Fifteen patients with planned canaloplasty and no intraoperative complications were included in this prospective study. AS-OCT images were acquired at 1, 3, 6 months and at a long-term time point (20±4.9 mo) postsurgery. UBM images were acquired at 3, 6 months and long-term after canaloplasty. The surgical site was evaluated for the presence of SC, transscleral filtration, a scleral lake, and the visibility of intra-Schlemm sutures. The SC's height and width were measured at the 3 and 9 o'clock limbus position. Results: Following canaloplasty, the intraocular pressure was successfully reduced from 23.43±5.52 to 12.6±1.78 mm Hg ( P <0.0001) at the final control visit. Topical medication was reduced from 2.9±1.1 to 0.4±0.6 over the same period. SC's increase in height was higher than that in width at the last visit (height: +351%, P= 0.0004, width: +144%, P= 0.002). With the UBM the SC was easily identifiable by the reflection of the tractions sutures in 75% of the patients at the last visit. Transscleral filtration was detectable in 42% of the patients at the last visit using AS-OCT and a scleral lake was still detectable by OCT in 25% of the patients and even in 42% of the patients by UBM. Conclusions: Persisting anatomic changes of SC, a transscleral filtration and a scleral lake can be recorded by AS-OCT and UBM long-term after successful canaloplasty.